2016
DOI: 10.1007/s11606-015-3579-9
|View full text |Cite
|
Sign up to set email alerts
|

Association of Opioids with Falls, Fractures, and Physical Performance among Older Men with Persistent Musculoskeletal Pain

Abstract: BACKGROUND: Although older adults are disproportionately affected by painful musculoskeletal conditions and receive more opioid analgesics than persons in other age groups, insufficient evidence is available regarding opioid harms in this age group. OBJECTIVE: To examine longitudinal relationships between opioid use and falls, clinical fractures, and changes in physical performance. We hypothesized that opioid use would be associated with greater risks of falling and incident clinical fractures and greater dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
2
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 39 publications
1
20
2
7
Order By: Relevance
“…As in our study, a recent analysis of 2900 male patients from the US assessed over 65 years (Krebs et al., ) could not show a significant relation between opioid intake and fractures. Furthermore, a longitudinal study from Denmark assessing drug intake (Jensen et al., ), in which patients were interviewed over the course of 9 years, did not find an effect of opioid intake on the risk of fracture and even showed that patients with opioid intake were in an overall poorer physical condition compared to patients who did not take opioid medication.…”
Section: Discussionsupporting
confidence: 51%
“…As in our study, a recent analysis of 2900 male patients from the US assessed over 65 years (Krebs et al., ) could not show a significant relation between opioid intake and fractures. Furthermore, a longitudinal study from Denmark assessing drug intake (Jensen et al., ), in which patients were interviewed over the course of 9 years, did not find an effect of opioid intake on the risk of fracture and even showed that patients with opioid intake were in an overall poorer physical condition compared to patients who did not take opioid medication.…”
Section: Discussionsupporting
confidence: 51%
“…However, other studies did not find a significant association between opioid use and falls, [18][19][20] and none examined this in severely injured older people who are at higher risk of death.…”
mentioning
confidence: 90%
“…Postural control refers to control of the body's position in space for the purposes of stability and orientation (4). Falls and fractures are commonly caused by deficient postural control (5,6). Patients with osteoporosis have an increased risk of falls, due to muscle weakness,…”
Section: Methodsmentioning
confidence: 99%